Customization of flexographic printing plates related to uvc-induced changes in the crosslinking degree - Tamara Tomašegović (Acta Graphica, 2016)
In this paper, the swelling properties of photopolymer flexographic printing plates related to the variations of UVC post-treatment have been analysed. The aim of the research was to interconnect the changes in the crosslinking degree of the photopolymer material occurring due to the modified UVC radiation of the printing plate and the changes of its surface free energy crucial in the graphic reproduction process. Changes in the crosslinking degree in the photopolymer materials have been analysed by the swelling experiments. Results have proven that the partial dissolution of the photopolymer material caused by the immersion of the printing plates in various solvents is in the direct relation with the changes of the dispersive surface free energy. UVC post-treatment, used for the crosslinking termination and the definition of the surface properties of printing plates, is therefore directly affecting the resistivity of the printing plate in the solvent environment. By calculating the correlation coefficients for the weight loss of the photopolymer material in solvents and the dispersive surface free energy, the relation between the crosslinking degree and the UVC post-treatment has been established.